80.4k views
0 votes
-4=-2/3u solve for U

-4=-2/3u solve for U-example-1
User Madav
by
4.6k points

1 Answer

5 votes

Answer:

u = 6

Explanation:


-(2)/(3)u=-4\qquad\text{change the signs}\\\\(2)/(3)u=4\qquad\text{multiply both sides by}\ (3)/(2)\\\\(3\!\!\!\!\diagup^1)/(2\!\!\!\!\diagup_1)\cdot(2\!\!\!\!\diagup^1)/(3\!\!\!\!\diagup_1)u=4\!\!\!\!\diagup^2\cdot(3)/(2\!\!\!\!\diagup_1)\\\\u=(2)(3)\\\\u=6

User Xinyu Li
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.